LUMBAR FACET ARTHROPLASTY FOR SPONDYLOLISTHESIS SURGICAL CORRECTION: SUMMARY OF EVIDENCES - Rafael Augusto da Silva Aparício; Felipe de Almeida Pinto; Rafael Félix Alves; Victor Hugo Cordeiro Ribeiro (Acta Ortopédica Brasileira)
ABSTRACT In persistent and debilitating cases of spondylolisthesis, surgical correction is usually indicated, and the surgeon may opt for spinal fusion or dynamic stabilization techniques, such as lumbar facet arthroplasty (LFA). However, LFA is an emerging technique that requires more research to fully understand its effectiveness and safety. To summarize the scientific evidence related to LFA in the surgical correction of spondylolisthesis. The database chosen to papers selection was PUBMED, based on the following search string: ((lumbar[title/abstract] AND facet[title/abstract] AND arthroplasty[title/abstract]) OR tops[title /abstract]) AND spondylolisthesis[title/abstract], including studies published in the last 10 years. Results: Initially, 9 papers were identified that met the previously established search strategy. After reading the titles and abstracts, 1 text was excluded because it did not deal with the application of LFA in spondylolisthesis, leaving 8 studies for review. Significant clinical improvement, maintenance of radiological stability and low complication rates were consistently observed with the use of LFA. Furthermore, economic analyzes indicated that the TOPS System is a cost-effective and economically dominant option compared to conventional approaches such as TLIF. These findings suggest that the TOPS system may be a viable and advantageous alternative for patients with degenerative spondylolisthesis, offering not only clinical but also long-term economic benefits. Level of Evidence IV; Descriptive Studies.